Rancang Bangun Host Sistem Mini SCADA Untuk Pengontrolan Beban Trafo 20 KV Pada Gardu Induk - Ikhwanto Ikhwanto; R. A. Kusumoputro; Novi Azman (Universitas Nasional, 2013)
In this era of globalization, the needs of remote control systems is increasing, where the system used is more sophisticated. Similarly, when a transformer operator in electrical substations, which will control and monitor the load transformer 20 KV is still done by hand. This will result in less efficient and optimal performance of the operator. We need a system that can control remotely. To overcome these problems, hence designed